EVALUATING METHANE EMISSION QUANTIFICATION STRATEGIES FOR DECARBONIZATION IN UPSTREAM OIL AND GAS BASED ON THE OGMP 2.0 FRAMEWORK: A DECISION MAKING ANALYSIS AT PT BLUE ENERGI - William Sukyono; Pri Hermawan (RADJA PUBLIKA, 2026)
Methane is a potent greenhouse gas with a global warming potential more than 80 times that of carbon dioxide over a 20-year horizon, making methane mitigation a priority for near-term decarbonization in the oil and gas industry. PT Blue Energi, an Indonesian upstream operator, joined the Oil and Gas Methane Partnership (OGMP) 2.0 in 2025 and targets the Level 5 Gold Standard, which requires a transition from emission-factor reporting (Levels 2-3) to source-level quantification (Level 4) and reconciled site-level measurement (Level 5). This study evaluates methane quantification strategies through a mixed-methods design combining qualitative situational analysis (SWOT and Kepner-Tregoe) with the Analytic Hierarchy Process (AHP). Pairwise-comparison data from ten subject-matter experts were aggregated by geometric mean, with priority weights derived from the principal eigenvector and consistency verified for every matrix. The results are source- and level-specific: at Level 4, Quantitative Optical Gas Imaging (QOGI) ranked first for fugitives (34.7%), process simulation using UniSim for flares (35.1%), and engineering calculation with QOGI for venting (40.1%); at Level 5, drone survey ranked highest (35.3%). All matrices satisfied the consistency requirement (CR < 0.10) and rankings were robust under sensitivity analysis, offering PT Blue Energi a replicable, expert-based framework for measurement-based methane reporting.